Sinergi Civitas Akademika STIT Mumtaz Karimun dalam pengabdian masyarakat melalui donasi untuk korban banjir di Aceh dan Sumatra - Siti Hawa; Ahmad Yani; Muhazir Abdul Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The natural disasters that hit the Aceh and Sumatra regions at the end of 2025 require a quick response to help the victims. This community service activity aims to collect and distribute aid in a targeted manner to survivors in Aceh Tamiang and Central Tapanuli. The method used is a community-based approach with three main stages: collecting data on needs, raising funds, and distribution through partnership channels. As a result, within a period of 12 days (2-13 December 2025), the team succeeded in collecting funds amounting to IDR 13,800,000 as well as various logistical assistance, such as clothing suitable for use. All aid was distributed in collaboration with BAZNAS Karimun, BMH, and the alumni network, who served as volunteers at disaster locations. The evaluation shows that the involvement of alumni and official institutions is very effective in ensuring transparency and speeding up the delivery of aid to people in need. This activity proves that synergy between universities and social institutions has an important role in strengthening solidarity and accelerating the post-disaster community recovery process.